COOPERATION OF UKRAINIAN SOCIETY FOR SOIL MECHANICS, GEOTECHNICS AND FOUNDATION ENGINEERING WITH INTERNATIONAL SOCIETY ISSMGE - Kryvosheiev, P. I.; Kozeletskiy, P. M.; Senatorov, V. M.; Kornienko, M. V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Information about cooperation of Ukrainian Society for Soil Mechanics, Geotechnics and Foundation Engineering with International Society for Soil Mechanics and Geotechnical Engineering, the results of Ukrainian society activity and prospects of its development are presented in paper. It is considered participation of Ukrainian specialists in International and regional conferences; results of the ninth All-Ukrainian scientific and technical conference «Soil mechanics, geotechnics and foundation engineering: problems, innovations and implementation of Eurocodes in Ukraine» and prospects of Ukrainian society development.
Keywords: International society for soil mechanics and geotechnical engineering; Ukrainian society for soil mechanics; geotechnics and foundation engineering